A novel fast heuristic to handle large-scale shape clustering. Issue 1 (2nd January 2016) - Ismkhan, Hassan
Abstract : Clustering algorithms like types of k -means are fast, but they are inefficient for shape clustering. There are some algorithms, which are effective, but their time complexities are too high. This paper proposes a novel heuristic to solve large-scale shape clustering. The proposed method is effective and it solves large-scale clustering problems in fraction of a second.